Pelatihan Penyusunan Modul Ajar Berbasis Muatan Lokal Kurikulum Merdeka Bagi Guru Sd Negeri 4 Kayuagung: Pengabdian - Sylvia Lara Syaflin; Puji Ayurachmawati; Sunedi (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The purpose of this PkM is to provide workshop training on the preparation of teaching materials based on local content in implementing the Merdeka Curriculum for SD Negeri 4 OKI teachers. The partner school for this activity is SD Negeri 4 Kayuagung, Ogan Komering Ilir Regency. The subjects involved in this activity were 35 teachers. The method used was workshops and question and answer discussions. This activity is felt to be very beneficial for teachers as educators in elementary schools, especially the independent learning curriculum is a new curriculum so that teachers still need to be given training on teaching materials, especially those based on local wisdom. Based on the results of the average questionnaire 91% of teachers can state that they are very happy with the independent learning flow training in understanding the profile of Pancasila students. Another 9% said they were happy.